Evaluation of diaper waste combustion efficiency in a steam-pressed oil waste stove-based incinerator with two air intakes - Ibnu Irawan; Khamdi Mubarok; Rifky Maulana Yusron; Rullie Annisa (Politeknik Negeri Lhokseumawe, 2026)
Waste such as used diapers remains a persistent environmental challenge that requires effective waste management solutions. This study aims to evaluate the performance and efficiency of an incinerator using diapers as the primary waste material. An incinerator can reduce waste volume and mass by converting it into ash. This experimental study using used oil and cooking oil as fuels for a steam-pressurized burner system. Variations in two-tiered air intakes are also used as a measure of evaluation of air velocity, which are 6 m/s, 8 m/s, and 10 m/s. The results demonstrates that for used oil fuel, average combustion temperatures of 376°C, 405°C, and 452°C were obtained at 6, 8, and 10 m/s, with combustion times of 97, 75, and 56 min, respectively. Residual ash masses were 1.01, 0.80, and 0.60 kg. For used cooking oil fuel, average temperatures reached 325°C, 354°C, and 387°C, with combustion times of 120, 107, and 86 min, respectively. Residual ash masses were 1.20, 1.08, and 0.85 kg. The results show that increasing air velocity significantly improved combustion temperature and reduced burning time for both fuels, while its effect on ash residue was less pronounced. Used oil produced higher combustion temperatures and faster waste reduction, whereas the highest thermal efficiency of 70% was achieved using used cooking oil at an air velocity of 10 m/s.